Multimodality Imaging Assessment of Tetralogy of Fallot: From Diagnosis to Long-Term Follow-Up - Sara Moscatelli; Valeria Pergola; Raffaella Motta; Federico Fortuni; Nunzia Borrelli; Jolanda Sabatino; Isabella Leo; Martina Avesani; Claudia Montanaro; Elena Surkova; Massimo Mapelli; Marco Alfonso Perrone; et al. (MDPI AG, 2023)
Tetralogy of Fallot (TOF) is the most common complex congenital heart disease with long-term survivors, demanding serial monitoring of the possible complications that can be encountered from the diagnosis to long-term follow-up. Cardiovascular imaging is key in the diagnosis and serial assessment of TOF patients, guiding patients' management and providing prognostic information. Thorough knowledge of the pathophysiology and expected sequalae in TOF, as well as the advantages and limitations of different non-invasive imaging modalities that can be used for diagnosis and follow-up, is the key to ensuring optimal management of patients with TOF. The aim of this manuscript is to provide a comprehensive overview of the role of each modality and common protocols used in clinical practice in the assessment of TOF patients.